2021
DOI: 10.3390/plants10122581
|View full text |Cite
|
Sign up to set email alerts
|

Gallotannin-Enriched Fraction from Quercus infectoria Galls as an Antioxidant and Inhibitory Agent against Human Glioblastoma Multiforme

Abstract: In recent years, herbal medicine has experienced rapid development in the search for alternative anticancer compounds. Various phytochemicals present in Quercus infectoria (QI) galls have been reported to trigger cytotoxic effects on many types of cancer cells. However, a specific active constituent of QI galls with the potential to inhibit highly invasive stage IV malignant brain tumor, glioblastoma multiforme (GBM), is yet to be discovered. In this study, a two-phase system composed of aqueous soxhlet extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Another group of compounds with high anti-GBM activity is gallotanins, for example, found in Quercus infectoria galls [102,103]. Kamarudin et al obtained the fractioned extract rich in gallotanins and showed its high cytotoxicity (IC 50 15.0 µg/mL) in the in vitro tests using the DBTRG-05MG cell line.…”
Section: Unraveling the Emerging Role Of Less Studied Plant-derived S...mentioning
confidence: 99%
“…Another group of compounds with high anti-GBM activity is gallotanins, for example, found in Quercus infectoria galls [102,103]. Kamarudin et al obtained the fractioned extract rich in gallotanins and showed its high cytotoxicity (IC 50 15.0 µg/mL) in the in vitro tests using the DBTRG-05MG cell line.…”
Section: Unraveling the Emerging Role Of Less Studied Plant-derived S...mentioning
confidence: 99%
“…Additionally, more studies need to assess the efficacy of phytochemicals against TMZ, the current therapeutic standard of care for GBM. From the studies included in this review, only four studies compared the cytotoxicity of phytochemicals to TMZ [140,159,161]. Mann Whitney-U testing demonstrated a statistically significant difference between the concentrations of natural extracts and phytochemicals required to reach IC50 versus TMZ.…”
Section: Natural Extract and Phytochemical Efficacy Against Glioblast...mentioning
confidence: 99%
“…In this study, it was found that the result of anticancer activity of the methanolic extract of the stem bark of Senna alata (Gelenggang) varied between previous studies due to different types of cancer cell lines used by both studies: MCF-7 breast cancer cells and PC-3 prostate cancer cell lines which then resulting in two different cytotoxic effects which are moderate and weak with IC 50 values at 47.11 µg/mL and 427.77 µg/mL, respectively (Madankumar et al, 2020;Kamarudin et al, 2021). Another study also reported that the different anticancer activity of ethanolic extract of Morinda citrifolia (Mengkudu) fruit on different cancer cell lines: THP-1 human monocyte cell and MDA-MB-231 breast cancer cell line resulting in different IC 50 values at 0.39 µg/mL (highly active) and 49.72 µg/mL (moderately active), respectively (Tsao et al, 2020;Vyn et al, 2020).…”
Section: Anticancer Activity Of Malaysian Medicinal Plants (In Vitro)mentioning
confidence: 99%